2000
DOI: 10.1103/physrevb.61.54
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical approach to the magnetostructural correlations in the spin-Peierls compoundCuGeO3

Abstract: A theoretical density-functional study has been carried out to analyze the exchange coupling in the chains of CuGeO 3 using discrete models. The results show a good agreement with the experimental exchange coupling constant ͑J͒ together with a strong dependence of J with the Cu-O-Cu angle. The calculation of the J values for a distorted model indicates a larger degree of dimerization than those reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The actual angle for which the crossover from antiferro- to ferromagnetic interaction appears varies with the nature and number of substituents at the bridging oxygens. For a trinuclear model of CuGeO 3 , in which each oxo bridge is attached to two Ge atoms, ferromagnetism is predicted at θ < 98°, practically the same angle found for hydroxo-bridged binuclear complexes but for unsubstituted oxo bridges, the crossover appears at θ ≈ 108° .…”
Section: Resultsmentioning
confidence: 57%
“…The actual angle for which the crossover from antiferro- to ferromagnetic interaction appears varies with the nature and number of substituents at the bridging oxygens. For a trinuclear model of CuGeO 3 , in which each oxo bridge is attached to two Ge atoms, ferromagnetism is predicted at θ < 98°, practically the same angle found for hydroxo-bridged binuclear complexes but for unsubstituted oxo bridges, the crossover appears at θ ≈ 108° .…”
Section: Resultsmentioning
confidence: 57%
“…Similar effects were recently illustrated in the spin-Peierls compound CuGeO 3 . 20 Considering the VPO monoclinic phase structure, 18 noticeable differences in the angular parameters characterizing the exchange pathways of D O and D OPO dimers can be found not only between its two structurally inequivalent chains, we note A and B, but also within each chain. Therefore, if one wants to amply consider magnetostructural correlations in VPO, two questions immediately arise: ͑1͒ How are the exchange parameters influenced by small structural differences in D O or D OPO dimers for two chains or within one chain ?…”
Section: Introductionmentioning
confidence: 87%
“…23 By taking the BS state as a raw estimate of the real singlet state, we do not take into account contamination arising from the triplet state. Despite the apparent alogism of such a choice, 24 Ruiz et al, [19][20][21] have shown that the nonspin-projected equation JϭE T ϪE BS leads to a better agreement with the experimental data than the spin projected equation does. Concerning the use of BS methods, one can refer to recent methodological works 21,[23][24][25] for an overview of the current state of the art.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In case of materials with covalent bonds such as CuGeO 3 , the embedding procedure with formal charges does not lead to meaningful results and alternative embedding schemes should be applied. 25,26 In the results section, we will shortly come back to the influence of the Madelung potential on the properties studied here.…”
Section: Computational Informationmentioning
confidence: 99%